PH Controlled Intersystem Crossing and Singlet Oxygen Generation of 8‐Azaadenine in Aqueous Solution. Issue 5 (15th February 2019) - Zhou, Zhongneng; Hu, Zhubin; Zhang, Xianwang; Jia, Menghui; Wang, Xueli; Su, Hongmei; Sun, Haitao; Chen, Jinquan; Xu, Jianhua
Abstract: Azabases are intriguing DNA and RNA analogues and have been used as effective antiviral and anticancer medicines. However, photosensitivity of these drugs has also been reported. Here, pH‐controlled intersystem crossing (ISC) process of 9H 8‐azaadenine (8‐AA) in aqueous solution is reported. Broadband transient absorption measurements reveal that the hydrogen atom at N9 position can greatly affect ISC of 8‐AA and ISC is more favorable when 8‐AA is in its neutral form in aqueous solution. The initial excited ππ* (S2 ) state evolves through ultrafast internal conversion (IC) (4.2 ps) to the lower‐lying nπ* state (S1 ), which further stands as a door way state for ISC with a time constant of 160 ps. The triplet state has a lifetime of 6.1 μs. On the other hand, deprotonation at N9 position promotes the IC from the ππ* (S2 ) state to the ground state (S0 ) and the lifetime of the S2 state is determined to be 10 ps. The experimental results are further supported by time‐dependent density functional theory (TDDFT) calculations. Singlet oxygen generation yield is measured to be 13.8 % for the neutral 8‐AA while the deprotonated one exhibit much lower yield (<2 %), implying that this compound could be a potential pH‐sensitized photodynamic therapy agent. Abstract : pH controlled intersystem crossing and singlet oxygen generation are found in 8‐azaadenine (8‐AA). Neutral form 8‐AA possess significant triplet state yield and moderate singlet oxygen yield. (see picture) The lifetime for intersystem crossing is determined to be 160 ps. As for deprotonated 8‐AA, efficient internal conversion is dominant with a lifetime of 10 ps and barely no singlet oxygen is generated.